Peran Orang Tua dalam Proses Pendidikan Anak Usia Dini di RA. Pozuhra - Fitri Almaida; Nur Hafiza; Praja Winata; Vivi Kartika Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Early childhood education is an important foundation in child development. One of the key factors in the success of early childhood education is the role of parents. This article aims to explore and analyze the role of parents in the early childhood education process in RA. Pozuhra. The research method used is qualitative research using observation and interview techniques with parents and teachers at RA. Pozuhra. Research findings show that the role of parents has a significant impact on early childhood development, including in social, emotional and cognitive aspects. Parents in RA. Pozuhra acts as a partner in education, supporting children's learning and reinforcing the values ​​taught in schools. The implication of this research is the importance of actively involving parents in the early childhood education process to improve the quality of education and ensure children's holistic development.